Mid-Term Evaluation of iStent Inject® Trabecular Micro-Bypass Stent Implantation with or without Phacoemulsification: A Retrospective Study - Silveira Seixas RC (Dove Medical Press, 2020)
Regina Cele Silveira Seixas,1 Marcos Balbino,2 Alberto Basile Neto,3 Amanda de Alcantara Almeida Costa,4 Marcelo Lopes da Silva Jordão,5 Heloisa Helena Abil Russ6 1HCloe Oftalmologia Especializada, Universidade Federal de São Paulo, São Paulo, SP, Brazil; 2HCloe Oftalmologia Especializada, Centro Universitário São Camilo, São Paulo, SP, Brazil; 3Clínica Oftalmológica do Complexo Hospitalar Padre Bento de Guarulhos, Guarulhos, SP, Brazil; 4Clínica Oftalmológica do Complexo Hospitalar Padre Bento de Guarulhos, Guarulhos, Universidade Estadual de Campinas, Campinas, SP, Brazil; 5Hospital das Clínicas da Faculdade de Medicina de Ribeirão Preto Medical School, Universidade de São Paulo, Ribeirão Preto, Brazil; 6HR Oftalmologia, Universidade Federal do Paraná, Curitiba, PR, BrazilCorrespondence: Marcos BalbinoHCloe Oftalmologia Especializada, Centro Universitário São Camilo, Cipriano Barata 1869 Ap. 93, São Paulo, SP, BrazilTel +55 11983462354Email marcosbalbino@mac.comIntroduction: This study evaluated the 6-month performance and safety of micro-invasive glaucoma surgery (MIGS) with iStent inject either with or without cataract surgery.Material and Methods: Longitudinal retrospective study of 86 surgeries in 49 patients with inadequately controlled open-angle glaucoma (OAG) or ocular hypertension who underwent iStent inject trabecular micro-bypass implantation either alone (isolated group) or combined with cataract surgery (combined group). The two primary outcomes included an intraocular pressure (IOP) drop of ≥ 20% versus preoperative values (adequate drop) and IOP maintenance between 6 and 18 mmHg (adequate Range). For both outcomes, we determined “complete” and “qualified” success if patients did not require or did require glaucoma medications, respectively, at the end of follow-up. Safety outcomes included best-corrected visual acuity, adverse events, and secondary surgeries.Results: In the adequate drop analysis, 30.2% achieved “complete success,” and 37.2% achieved “qualified success.” For adequate range, 40.7% achieved “complete success” and 39.5% achieved “qualified success.” There was no difference in medication decrease (p=0.77) nor IOP reduction (p=0.46) between the isolated and combined groups. Safety was generally favorable and similar between groups, with mild transient adverse events that resulted in no sequelae.Discussion/Conclusion: iStent inject implantation either with or without cataract surgery was able to safely decrease IOP and medication requirements through 6 months after surgery.Keywords: glaucoma, medical treatment, trabecular micro-bypass, glaucoma surgery combined with cataract surgery, micro-invasive glaucoma surgery